Mechanics of materials - Goodno, Barry J. (Cengage, 2021)
Develop a thorough understanding of the mechanics of materials - an area essential for success in mechanical, civil and structural engineering -- with the analytical approach and problem-solving emphasis found in Goodno/Gere's leading MECHANICS OF MATERIALS, ENHANCED, 9th Edition. This book focuses on the analysis and design of structural members subjected to tension, compression, torsion and bending. This ENHANCED EDITION guides you through a proven four-step problem-solving approach for systematically analyzing, dissecting and solving structure design problems and evaluating solutions. Memorable examples, helpful photographs and detailed diagrams and explanations demonstrate reactive and internal forces as well as resulting deformations. You gain the important foundation you need to pursue further study as you practice your skills and prepare for the FE exam.